THE INFLUENCE OF THE COVID-19 PANDEMIC ON THE PEOPLE'S ECONOMY IN WEST SUMATRA - Engla Desnim Silvia; Anatia Agusti (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
This study aims to see how much influence the Covid-19 pandemic has had on the people of West Sumatra. All economic activity has decreased, during the PSBB economic activities were stopped and all activities were restricted, causing unemployment to increase. The impact of the pandemic has had a major impact on income levels. Households with low income have increased and those with middle and upper income have decreased. Of course, as a result of this, income inequality in West Sumatra has slightly decreased. The decline in economic activity affected by the Covid 19 pandemic has different characteristics from the economic crises experienced in 1998 and 2008. The impact that occurred as a result of Covid 19 was a sharp decline in economic activities that required physical interaction. Where economic growth declined sharply, inflation rose and unemployment and poverty also increased. The pandemic directly disrupted the production and spending side of society. The main finding of this study is that West Sumatra is not affected by Covid too much when compared to other regions. However, in the post-covid-19 pandemic period, expectations were quite high for economic improvement in the post-covid1-9 pandemic period.